Printed dipole array for Wireless local area network (WLAN) communication - Aiza Mahyuni, Mozi (Universiti Malaysia Perlis, 2008)
Wireless Local Area Network (WLAN) communication requirements continue to push for a higher gain and more bandwidth capabilities of antenna system. At the same time, the antenna must satisfy the technical requirements for high performance and being lightweight as well as the need to meet the additional economic constraints of simplicity and reliability. In fulfilling the demands, printed dipole array antenna for WLAN communication project proposes to develop microstrip dipole antenna in uniform collinear array configuration operating in 2.45 GHz. This microstrip dipole array antenna is constructed by assembling two and four elements of identical dipole antennas in a single line. Each dipole antenna is arranged with uniform spacing to form a (2 x 1) and (4 x 1) uniform collinear array structure. The microstrip dipole array antenna is printed on ferrite substrates of 36 microns thickness and feed using proximity coupling method. The antenna design, simulated and measured dipole array antennas return loss and radiation pattern are deliberated within this report.